Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jof8040339
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tocilizumab and Invasive Aspergillosis in Critically Ill Patients with Severe COVID-19 Pneumonia and Acute Respiratory Distress Syndrome

Abstract: Coronavirus disease-2019 (COVID-19) causes severe pneumonia and acute respiratory distress syndrome. According to the current consensus, immunosuppressants, such as dexamethasone and anti-interleukin-6 receptor monoclonal antibodies, are therapeutic medications in the early stages of infection. However, in critically ill patients, viral, fungal, and bacterial coinfection results in higher mortality. We conducted a single-center, retrospective analysis of 29 mechanically ventilated patients with artificial airw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…These findings indicated that CAPA was not uncommon among patients with critical COVID-19 in the ICUs, and the mortality of CAPA remained high. Similar findings were shown in the two other series in Taiwan [ 5 , 6 ]. A single-center, retrospective study by Wu et al reported that 6 (20.7%) of 29 mechanically ventilated COVID-19 patients with severe pneumonia had coinfection with CAPA based on elevated serum galactomannan levels and/or bronchoalveolar lavage fluid [ 5 ].…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These findings indicated that CAPA was not uncommon among patients with critical COVID-19 in the ICUs, and the mortality of CAPA remained high. Similar findings were shown in the two other series in Taiwan [ 5 , 6 ]. A single-center, retrospective study by Wu et al reported that 6 (20.7%) of 29 mechanically ventilated COVID-19 patients with severe pneumonia had coinfection with CAPA based on elevated serum galactomannan levels and/or bronchoalveolar lavage fluid [ 5 ].…”
supporting
confidence: 91%
“…This present Special Issue of the Journal of Fungi addresses the clinical interaction between viruses and fungi. Studies cover new epidemiological knowledge, diagnosis, and treatment of virus-associated fungal diseases, including fungal diseases with COVID-19 in four articles [ 3 , 4 , 5 , 6 ] and with Influenza A (H1N1) in two studies [ 7 , 8 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Aspergillus is the most well-established fungal infection associated with COVID-19, many less common fungal infections have since been reported. In contrast to aspergillosis, mucormycosis is historically rare following viral infection [59]. However, COVID-19-associated mucormycosis (CAM) is now the most widely reported non-Aspergillus mold infection [64•, 65••, 66, 67].…”
Section: Non-aspergillus Mold Infectionsmentioning
confidence: 99%